Tree growth, mortality and recruitment of stand dynamics over 10 years (2012-2022) in tropical forests, Phou Khao Khouay National Park, Laos - Phomphoumy, Khamphet Phomphoumy; Thi Thu Hien, Cao Thi Thu Hien; Doan Tuan Minh Thanh; Thi Nhung, Trinh Thi Nhung; Nanthavong, Khamseng; Millet, Jerome Millet; Satdichanh, Manichanh; Hong Hai, Nguyen (Journal of Forestry Science and Technology, 2024)
The present study delved into the dynamics of tree communities in a specific area within Phou Khao Khouay National Park in Laos, distinguished by three distinct tropical forest types: Dry Evergreen Forest (DEF), Mixed Deciduous Forest (MDF), and Mixed Coniferous Forest (MCF). Conducted over a decade, from 2012 to 2022, we utilized data from a previous inventory carried out in 32 permanent plots, each measuring 50 m × 50 m. Trees with a diameter at breast height (DBH) ≥ 10 cm were identified, tagged, and measured for various parameters. In 2012, we documented 4,072 stems, amounting to 395 species existing within 155 families across the 32 plots, with a total area of 8 ha. By 2022, the number of stems had increased to 4,402, but the species and family counts had decreased to 311 and 135, respectively. Over the ten years, there was a notable increase in the number of stems, basal area (BA), and aboveground biomass (AGB), accompanied by a reduction in species and families. This study contributes valuable insights that can be utilized to enhance forest management practices. The observed trends provide a nuanced understanding of the dynamic nature of the forest ecosystems in the study area. The findings underscore the importance of considering individual forest types when implementing conservation strategies.